2022
DOI: 10.1038/s41467-022-32685-3
|View full text |Cite
|
Sign up to set email alerts
|

An interplay between cellular growth and atypical fusion defines morphogenesis of a modular glial niche in Drosophila

Abstract: Neural stem cells (NSCs) live in an intricate cellular microenvironment supporting their activity, the niche. Whilst shape and function are inseparable, the morphogenetic aspects of niche development are poorly understood. Here, we use the formation of a glial niche to investigate acquisition of architectural complexity. Cortex glia (CG) in Drosophila regulate neurogenesis and build a reticular structure around NSCs. We first show that individual CG cells grow tremendously to ensheath several NSC lineages, emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 100 publications
0
24
0
Order By: Relevance
“…1D). CG network is progressively built around NSC during larval development in a process which parallels NSC behaviour [21,24,25] (Fig. 1E).…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…1D). CG network is progressively built around NSC during larval development in a process which parallels NSC behaviour [21,24,25] (Fig. 1E).…”
Section: Introductionmentioning
confidence: 78%
“…For the Nrx-IV antibody, CNS were fixed for 3 minutes in Bouin’s fixative solution (Sigma Aldrich, HT10132), and the rest of the protocol was identical. Primary antibodies used were: guinea pig anti-Dpn (1:5000,[25]), chicken anti-GFP (1:2000, Abcam ab13970), rat anti-ELAV (1:100, 7E8A10-c, DSHB), mouse anti-ELAV (1:100, 9F8A9-c, DSHB), rat anti-dE-cadherin (1:50, DCAD2, DSHB), mouse anti-Armadillo (1:50, N2 7A1, DSHB), rabbit anti-Repo (1:10000, kind gift from B. Altenheim), mouse anti-Repo 1:100 (DSHB, 8D12-c), mouse anti-Prospero (1:100, MR1A, DSHB), rabbit anti-Asense (1:3000, kind gift from the Yan lab). rabbit anti-Phospho-histone H3 (1:100, Millipore 06-570), rabbit anti-Nrx-IV (1:1000, [46]) mouse anti-wrapper (1:20, DSHB 10D3, supernatant), mouse anti-Nrg 180 (1:50, DSHB BP104, supernatant).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…3). Recently, it has been shown that cortical glia increases their nuclei number and extend membrane network through endomitosis (Rujano et al, 2022).…”
Section: Cut Defective Cortical Glial Cells Are Unable To Increase Th...mentioning
confidence: 99%